Aspectos perturbativos das teorias de calibre não-abelianas com a quebra da simetria de Lorentz - Silva, Antônio José Gomes Carvalho (2021)
In this thesis, we study the quantization problems of non-abelian gauge theories. In which, we work with theoretical models that contain a parameter that violates Lorentz (QSL) symmetry in the perturbative regime, that is, an axial vector b incorporated into the models and compute the non-abelian aether term for the dimensions 3D and 4D, we then incorporate the mass term (non-abelian aether) in 3D, found from the perturbative generation in Yang-Mills+Higgs theories with a constant background vector field, whose presence breaks Lorentz symmetry. The constant background vector is introduced in the term non-abelian aether. Finally, we show the influence of this aether coupling on the Yang-Mills most Higgs model and as a result we saw that for some values of it, the theory can be driven from a non perturbative to a perturbative regime.